Nasolacrimal System Aeration on Computed Tomographic Imaging: Sex and Age Variation. Issue 1 (January 2016) - Czyz, Craig N.; Bacon, Thomas S.; Stacey, Andrew W.; Cahill, Eva N.; Costin, Bryan R.; Karanfilov, Boris I.; Cahill, Kenneth V.
Abstract : Purpose: To investigate variation in aeration of the nasolacrimal drainage system between age groups and genders, and to report the reliability of repeated aeration grading and nasolacrimal canal measurements on CT. Methods: Retrospective review of CT images from 92 individuals, 60 female and 32 male, was conducted by 3 independent reviewers for the presence of air within the nasolacrimal drainage system. Diameter and area measurements were also obtained at the smallest identifiable portion of the nasolacrimal canal by 2 independent reviewers. Results: When air is present on CT, it is seen more fully throughout the nasolacrimal system in men as compared to women. Age data demonstrate that patients from the third and fourth decade have significantly more aeration than older patients. Diameter and area of the nasolacrimal duct within the canal at its narrowest point revealed no correlation with sex, age, or nasolacrimal system aeration. Inter-reviewer reliability shows strong repeatability of aeration grading and nasolacrimal duct measurements between multiple reviewers. Conclusions: The results suggest CT is reliable and repeatable modality to assess nasolacrimal system aeration and nasolacrimal duct diameter. Decreased aeration of the nasolacrimal system in females and the elderly mirrors epidemiologic trends for those at risk to develop primary acquired nasolacrimal duct obstruction. Variables in nasolacrimal drainage system anatomy, specifically nasolacrimal duct diameter and area, did not vary between sexes or age groups, suggesting aeration may be an overlooked variable in nasolacrimal system function. Abstract : Nasolacrimal system aeration as seen on CT decreases as age increases and is lower overall in females. Nasolacrimal canal diameter and area did not vary between sexes or age groups and had no correlation to aeration.